Rancang Bangun Sistem Informasi Administrasi Pelayanan Bidan Praktik Swasta (BPS) Di Puskesmas Plosoklaten Berbasis Web - Novita Kumalasari; A.B Tjandrarini; Pantjawati Sudarmaningtyas (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
The Plosoklaten Health Center supervises 11 midwives who are placed in 9 villages in Plosoklaten District. Each midwife has a place of practice called Private Practice Midwife (BPS). Services available at BPS include: Maternal and Child Health Services (KIA), women's reproductive health services, family planning (KB), and the Integrated Elderly Service Post (Posyandu Lansia). MCH services include: Pregnant women, postpartum mothers, and the Integrated Service Post for Under Five Years (Posyandu Toddler). The problem that occurs today is that each patient has more than one treatment card. Currently one medical card is only used for one service, while a patient can get more than one service at BPS. The registration process carried out at BPS is carried out for each service. If the patient does not bring a medical card, the midwife will look for a medical record card based on the patient's name, the process takes ±10 minutes. At the time of making the Local Area Monitoring report (PWS) if there is more than one midwife in one village, the midwives must complete each other's forms and this recording process lasts ±3 days. The solution given to this problem is to create a Web-based BPS Service Administration Information System at the Plosoklaten Health Center. Making this application using the Waterfall Model development method. This application has features to register patients, print patient treatment cards that can be used in all services, record examination results, and generate reports. Based on the results of testing the BPS service administration information system, which was carried out using the Black Box Testing Method, the application can create medical card numbering that can be used for all services, can be used to record examination results, and can generate reports to the head of the puskesmas. This can be proven by testing as many as 73 test cases which are 100% successful.